Comparison Of Production Cost Of House Between Making It Yourself Or Buying From Subcontracting At Pt. Benhard Bagus Bersama In Makassar - Hadi Wahyudi; Muh. Rum; Faidul Adzim (International Journal of Economic Research and Financial Accounting, 2024)
Building a house is one of the most important decisions in a person's life. This decision is often accompanied by careful financial considerations. This thesis aims to compare the Cost of Goods Sold of building a house yourself or buying from a subcontractor at PT. Benhard Bagus Bersama in Makassar.The research method used is a descriptive quantitative approach to management accounting. Data was collected through interviews, observations, and documentation.The results of the study show that the COGS of a self-built house is cheaper than the COGS of buying from a subcontractor. The difference in COGS between the two schemes is Rp 25,915,256 or 25.9%. The factors that cause this difference in COGS are cost efficiency, reduction of subcontractor's profit, and the risk borne by the buyer. The conclusion of this study is that the self-build scheme is more cost-effective than the subcontractor purchase scheme. However, the self-build scheme takes longer, requires expertise and experience, and has a higher risk. Therefore, potential buyers are advised to carefully consider these factors before choosing the scheme that best suits their needs and abilities.